Corrigendum to Examining Education, Culture, Health, and Workforce Characteristics of Turkish Provinces: A Cluster-Based Analysis - Serhat Peker; Elif Mutlu; Ümit Kuvvetli (Journal of Economic Policy Researches / İktisat Politikası Araştırmaları Dergisi, 2026)
Following publication, the authors identified errors in several in-text citations, portions of the literature review, and the reference list. The authors subsequently requested that these errors be corrected.The corrections are limited to citation and reference information and the corresponding text affected by these corrections. No changes have been made to the study’s methodology, dataset, analyses, results, discussion, or conclusions. Accordingly, these corrections do not affect the scientific findings or interpretations presented in the article.